BERBAGAI VARIASI KATA KERJA BENTUK -ING - Haryanti, Sri (MAGISTRA, 2010)
The verb ing form in English can be in several categories, such as verb, noun, adjective and adverb. As verb, verb ing form is as a predicate showing progressive tense, e.g. The children are playing football. As noun, verb ing form being given the name gerund functions as subject, e.g. Studying English is very important, as subjective complement, Our task is studying English, as object of verb The students enjoy studying English, as object of preposition All of us are interested in studying English. As adjective, verb ing form modifies noun, e.g. The studying students look serious. As adverb, verb ing form modifies a clause, e.g. Studying English, the students can know the references written in English. Verb ing form is also used in absolute construction, e.g. The students studying English, their horizons become expanding. Key words: verb ing form, adjective, gerund.